Sonogashira coupling reactions of bromomaleimides: route to alkyne/cis-Alkene/Alkyl maleimides: synthesis of luffarin X and cacospongionolide C - Deore, Prashant S.; N. P. Argade (Journal of Organic Chemistry, 2012)
Palladium-catalyzed Sonogashira coupling reaction of bromomaleimides with a diverse range of terminal alkynes has been demonstrated to furnish the corresponding alkynylmaleimides in very good yields. This coupling reaction followed by selective reduction of the triple bond to single bond have been utilized as the decisive steps to accomplish the first total synthesis of natural products (+/-)-luffarin X and (+/-)-cacospongionolide C.

Synthesis of chenopanone - Deore, Prashant S.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2014)
Starting from glyoxalic acid, a facile three step approach to chenopanone has been described utilizing the Barbier reaction as a key step.
Keywords: acid hydrolysis; Barbier reaction; chenopanone; condensation; Glyoxalic acid; isovaleraldehyde; synthesis

Synthesis of yangjinhualine A - Deore, Prashant S.; Batwal, Ramesh U.; N. P. Argade (Synthesis-Stuttgart, 2015)
Selective reduction of 3-(4-hydroxyphenyl)-2-methylmaleic anhydride provides access the corresponding gamma-hydroxybutenolide natural product yangjinhualine A.
Keywords: anhydrides; lactones; Natural products; reduction; Regioselectivity